"We are looking at the future right now": community acceptability of a home-based viral load test device in the context of HIV cure-related research with analytical treatment interruptions in the United States. Issue 1 (17th March 2022) - Dubé, Karine; Kanazawa, John; Roebuck, Christopher; Johnson, Steven; Carter, William B.; Dee, Lynda; Peterson, Beth; Lynn, Kenneth M.; Lalley-Chareczko, Linden; Hiserodt, Emily; Kim, Sukyung; Rosenbloom, Daniel; et al.
Abstract: Background: People with HIV (PWH) and community members have advocated for the development of a home-based viral load test device that could make analytical treatment interruptions (ATIs) less burdensome. Objective: We assessed community acceptability of a novel home-based viral load test device. Methods: In 2021, we conducted 15 interviews and 3 virtual focus groups with PWH involved in HIV cure research. We used conventional thematic analysis to analyze the data. Results: PWH viewed the home-based viral load test device as a critical adjunct in ongoing HIV cure trials with ATIs. The ability to test for viral load at home on demand would alleviate anxiety around being off ART. Participants drew parallels with glucometers used for diabetes. A preference was expressed for the home-based test to clearly indicate whether one was detectable or undetectable for HIV to mitigate risk of HIV transmission to partners. Perceived advantages of the device included convenience, sense of control, and no puncturing of veins. Perceived concerns were possible physical marks, user errors and navigating the logistics of mailing samples to a laboratory and receiving test results. Participants expressed mixed effects on stigma, such as helping normalize HIV, but increased potential for inadvertent disclosure of HIV status or ATI participation. Increasing pluri-potency of the device beyond viral load testing (e.g., CD4+ count test) would increase its utility. Participants suggested pairing the device with telemedicine and mobile health technologies. Conclusions: If proven effective, the home-based viral load test device will become a critical adjunct in HIV cure research and HIV care.